2011
DOI: 10.1097/ccm.0b013e318225761a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new acute kidney injury biomarkers in a mixed intensive care unit*

Abstract: This prospective observational study with a cohort of heterogeneous patients treated in a mixed intensive care unit revealed that new acute kidney injury biomarkers have a significantly and moderately predictive use for acute kidney injury diagnosis and that urinary L-type fatty acid-binding protein and neutrophil gelatinase-associated lipocalin can serve as new biomarkers of mortality prediction in critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
108
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 38 publications
11
108
3
3
Order By: Relevance
“…Lastly, urine Alb (uAlb) has also been investigated as an AKI biomarker. Matsui et al 57 found an AUC of 0.70 for uAlb regarding AKI prediction in a small study of 25 critically ill patients, while Doi et al 22 in a large study of 339 critically ill patients reported a similar AUC for uAlb (0.69). Another study found that uAlb in patients with prerenal AKI showed modest, but significantly higher concentrations than in patients with non-AKI.…”
Section: Kim-1 In the General Adult Icumentioning
confidence: 92%
See 4 more Smart Citations
“…Lastly, urine Alb (uAlb) has also been investigated as an AKI biomarker. Matsui et al 57 found an AUC of 0.70 for uAlb regarding AKI prediction in a small study of 25 critically ill patients, while Doi et al 22 in a large study of 339 critically ill patients reported a similar AUC for uAlb (0.69). Another study found that uAlb in patients with prerenal AKI showed modest, but significantly higher concentrations than in patients with non-AKI.…”
Section: Kim-1 In the General Adult Icumentioning
confidence: 92%
“…ROC curve analysis revealed an AUC of 0.993 for death prediction. Likewise, Doi et al 22 found an AUC of 0.90 for 14-day mortality for uL-FABP measured on ICU admission. The AUC of uL-FABP for AKI prediction 1 week post-ICU entry was 0.75.…”
Section: Interleukin-18mentioning
confidence: 99%
See 3 more Smart Citations